Manual teknologi penanaman sayuran secara sistem hidroponik Nutrient film technique - Yunus, Muhamad Fahmi; Ponari, Md Hoirul Azri; Shahari, Rozilawati; Salleh, Mohd Syahmi; Muhamad Tajudin, Nur Shuhada; Karim, Mohd Fauzihan (2021)
The disclosure contains a manual on how to run Nutrient Film Technique hydroponic set Hydroponic is a modern agriculture technique for plant growing without the use of soils